Investigation of a hydrophobically associating AMAHS polyacrylamides: A new corrosion inhibitor for mild steel in HCl. Issue 9 (23rd March 2020) - Rao, Xingxing; Zhou, Long; Zhang, Guanglong; Wang, Xuan; Xia, Shuwei; Yu, Liangmin
Abstract: A polyacrylamide with capsaicin‐derived monomers (AM–MAA–AMPS–HMBA–SMA; AMAHS) was synthesized and investigated as a novel environment‐friendly polymer inhibitor for Q235 mild steel at 25°C in 1 M HCl solution. The inhibition efficiency was evaluated by weight loss measurements, electrochemical experiments, and surface investigation methods as well as by theoretical calculations. Experimental results indicated that the efficiency of AMAHS was up to 94.86% at the concentration of 2 g/L. Electrochemical tests and surface morphology analysis showed that AMAHS served as a mixed‐type corrosion inhibitor, which could be adsorbed and self‐assembled on the surface of mild steel forming a highly hydrophobic protective film (contact angle of 172°). Density functional theory calculations revealed that heteroatoms in AMAHS, such as O, N, S, are active sites in forming coordination bonds with surface iron atoms. In addition, hydrophobic groups played an important role in protecting the metal surfaces from corrosion media. Abstract : This paper independently designed and synthesized a highly effective, low‐toxicity hydrophobically associating AMAHS. These studies not only extend the development of hydrophobically associating polymers as corrosion inhibitors, but also provide new ideas for the design of new efficient, long‐lasting, and environment‐friendly water‐soluble polymer inhibitors in the future.